2017
DOI: 10.1002/jso.24808
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence patterns and associated factors of locoregional failure following neoadjuvant chemoradiation and surgery for esophageal cancer

Abstract: Although aggressive tumor biology plays a significant role in LRR, optimizing neoadjuvant treatments to obtain a complete pathologic response may lead to improved locoregional control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 30 publications
4
15
0
Order By: Relevance
“…showed better local PFS in the CRT + surgery (two‐year PFS 64.3%, 95% CI 52.1–76.5%) than in the CRT group (two‐year PFS 40.7%, 95% CI 28.9–52.5%; P = 0.003) . Furthermore, some studies on esophageal SCC discovered that the amount of residual cancer, as measured by tumor regression grade, increased significantly after a longer interval between nCRT and surgery . This may have been one of the reasons why the short‐term outcome was less favorable in the non‐surgery than in the surgery group.…”
Section: Discussionmentioning
confidence: 99%
“…showed better local PFS in the CRT + surgery (two‐year PFS 64.3%, 95% CI 52.1–76.5%) than in the CRT group (two‐year PFS 40.7%, 95% CI 28.9–52.5%; P = 0.003) . Furthermore, some studies on esophageal SCC discovered that the amount of residual cancer, as measured by tumor regression grade, increased significantly after a longer interval between nCRT and surgery . This may have been one of the reasons why the short‐term outcome was less favorable in the non‐surgery than in the surgery group.…”
Section: Discussionmentioning
confidence: 99%
“…This was not consistent with the previous description in which a higher radiotherapy dose was required for the patients with a large tumor size ( 26 ). As previously described, pathological staging was a prognostic factor for EC ( 27 , 28 ). Nevertheless, in this study, TGLN with a diameter ≤2 cm (HR = 0.108; 95% CI, 0.047–0.249) and HFR (HR = 0.236; 95% CI, 0.105–0.528) were independent risk factors for better prognosis.…”
Section: Discussionmentioning
confidence: 98%
“…Several recent, single institution studies have identified characteristics that portend higher risk for recurrence and mortality after resection in esophageal adenocarcinoma which include high tumor grade, presence of LVI, and presence of perineural invasion. [13][14][15] Although these characteristics correlate with high risk factors as defined by the NCCN, no previous studies have validated that adjuvant therapy improves survival for patients with completely resected, pT2-4aN0M0 esophageal adenocarcinoma who have tumors with high risk characteristics. Despite the NCCN recommendations, our findings suggest there is no benefit to adjuvant therapy in these patients.…”
Section: Discussionmentioning
confidence: 99%